Jane Austen’s Concerns with Health and Moral Thoughts: The Dashwood Sisters and the Successful Regulation of Sense and Sensibility - González Mínguez, María Teresa (The Grove - Working Papers on English Studies, 2019)
According to Cartesian principles, in the seventeenth century the body was thought to be subordinated to the mind. Later in the eighteenth-century male authors of medical treatises supported the idea that the interaction of body and mind produced passion and could dangerously turn into mental breakdown. In all her novels Jane Austen showed an enormous interest in all matters concerning medical treatment. In Sense and Sensibility(1811), Austen emphasized illness and suffering by mixing physical health and mental disease with moral and philosophical doctrines. My contention in this article is that moralists, philosophers and thinkers such as Dr Johnson, William Blake, William Godwin, and Adam Smith collaborated with Austen to shape the idea that sensibility was no disease and sense no virtue; instead they propose that human beings, especially women, can obtain individual and collective profit and promote changes not only in the past but also in the present if they regulate their reason and feeling with a practical mindset.Key words: physical health, mental breakdown, medicine, moral thoughts, regulation of feelings.